Digital Service Impact on Islamic Bank Customer Loyalty in Urban Communities: A Comparative Study in Bandar Lampung and Metro - Muhammad Afnie Adam; Ahmad Hazas Syarif; Agus Kurniawan; Hotman Hotman (Journal of Islamic Digital Economic and Finance, 2026)
Objective: This study aims to analyze the impact of digital services, including mobile banking, internet banking, and app-based services, on customer loyalty in Islamic banks operating in urban areas. Bandar Lampung and Metro City in Lampung Province were selected as study locations to examine differences in digital banking adoption and customer behavior within distinct urban ecosystems. Method: This study employs a quantitative survey design using a Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS-SEM). A total of 320 active customers of Islamic banks in Bandar Lampung and Metro City were selected through purposive sampling. The variables examined include ease of use, transaction security, digital service quality, trust, customer satisfaction, and customer loyalty. Data analysis was conducted to assess direct, mediating, and moderating relationships among the variables. Result: The findings reveal that ease of use (β = 0.312, p < 0.01), transaction security (β = 0.289, p < 0.01), and digital service quality (β = 0.341, p < 0.01) positively and significantly influence customer satisfaction. Customer satisfaction serves as a strong mediating variable in the relationship between digital services and customer loyalty (β = 0.427, p < 0.001). Trust was also found to moderate this relationship significantly (β = 0.198, p < 0.05). Moreover, customers in Bandar Lampung exhibit higher levels of digital service adoption than those in Metro City. Implication: This study has practical implications for Islamic bank management, including increasing investment in digital infrastructure to build sustainable customer loyalty and developing structured digital literacy programs, particularly in areas with lower adoption rates, such as Metro City. Novelty: This study contributes to the literature by adopting a comparative urban ecosystem perspective, contrasting a regional economic center with a developing satellite city. It also integrates trust as a moderating variable within the PLS-SEM framework, providing a more comprehensive understanding of customer loyalty formation in the context of digitalization in Islamic banking in Indonesia.